Use of laser in Pediatric Dentistry frenectomy surgery: A scoping review (Research, Society and Development, 2024)
The frenulum is a fold of the buccal mucosa made up of fibrous or fibromuscular tissue covered by a mucous membrane and may present an anomaly and may limit movements of the tongue or lips. Ankyglossia is an anomaly in the lingual frenulum characterized by limited movement, altering speech and swallowing. The treatment of this anomaly is called frenectomy, which is a small surgery, where the frenulum is excised, so that that region can move without limitations. Since the use of laser in dentistry has been growing nowadays, it has been a great ally in frenectomy surgeries because it presents better trans and postoperative conditions. The objective of this study is to report, the current scenario of laser frenectomy in Pediatric Dentistry. Methodology: This study was carried out through a systematic scoping review, using the keywords Lip frenulum, Lingual frenum, Laser therapy and Pediatric dentistry, pointing out the applications of lasers in frenectomy surgery in pediatric patients. Results: The search found 18 studies and noting that laser frenectomy is a safe procedure to be used in Pediatric Dentistry. Conclusion: It is concluded that the use of laser in frenectomy in pediatric dentistry patients is very well accepted by patients and dentists in relation to conventional surgery because it is less invasive, without intercurrences and less bleeding, positively interfering with the patient’s quality of life.